Cefaclor, a cephalosporin antibiotic, delays gastric emptying rate by a CCK-A receptor-mediated mechanism in the rat - (:unkn) unknown (NATURE PUBLISHING GROUP, 2000)
1 Studies in vitro suggest that cephalosporin antibiotics release the gut hormone cholecystokinin. Cholecystokinin is known to inhibit gastric emptying. Here we examine the effects of cefaclor on gastric emptying and intestinal motility. 2 Male Sprague-Dawley rats were fitted with gastric cannulas. Following a 3-week recovery, the rate of gastric emptying of saline, peptone (4.5%) or cefaclor was determined after instillation into the gastric cannula, while intestinal transit was measured by using the propagation of arabic gum + charcoal mixture given intraduodenally. 3 Gastric emptying of saline was significantly delayed by the addition of cefaclor (3, 10, 30 or 100 mM). The CCK-A antagonist SR-27897B (1 mg kg(-1), i.p.) reversed the delay induced by 10 mM cefaclor, whereas the CCK-B antagonist CI-988 (1 mg kg(-1), i.p.) had no significant effect. In capsaicin-treated rats, 10 mM cefaclor emptied more rapidly than in vehicle-treated animals. 4 Thirty-minute intestinal transit was increased at 30 and 100 mM of cefaclor, while the gastric acid secretion following cefaclor instillation was no different than the group which received saline. 5 The cephalosporin antibiotic cefaclor appears to be a potent stimulant of CCK release from gut endocrine cells, resembling the effects of peptone. Cefaclor delays gastric emptying via capsaicin-sensitive afferent pathways, which involve CCK-A receptor interaction.
Keywords: cephalosporins; gastric emptying; cholecystokinin (CCK); CCK-A receptors; capsaicin; STIMULATE CHOLECYSTOKININ SECRETION; PANCREATIC ENZYME SECRETION; TRYPSIN-INHIBITOR; DIABETIC GASTROPARESIS; FEEDBACK-REGULATION; SENSORY NEURONS; MONITOR PEPTIDE; BINDING-SITES; STC-1 CELLS; ERYTHROMYCIN